Symbolic ineffective criminal law and state constitutional emergency to fight crime - Zavala Van Oordt, Lizet (2017)
In this article the author analyzes the sterility of so-called Criminal Law Symbolic  and the ineffectiveness of one of its recurring expressions in our reality, as is the declaration of a state of constitutional emergency, to fight crime, apropos of the recent experience lived in the Province Constitutional Callao, and highlights the misuse of a repressive, vindictive and devoid of reasonable criminal policy; in order to conclusively reaffirm the ethical duty and constitutional obligation of every democratic state and right criminological design and implement a policy respecting the dignity of the human person is effective to control and reduce crime.